Stress Analysis of a Class II MO-Restored Tooth Using a 3D CT-Based Finite Element Model - Yiu Pong Chan; Chak Yin Tang; Bo Gao (International Journal of Biomaterials)
A computational method has been developed for stress analysis of a restored tooth so that experimental effort can be minimized. The objectives of this study include (i) developing a method to create a 3D FE assembly model for a restored tooth based on CT images and (ii) conducting stress analysis of the restored tooth using the 3D FE model established. To build up a solid computational model of a tooth, a method has been proposed to construct a 3D model from 2D CT-scanned images. Facilitated with CAD tools, the 3D tooth model has been virtually incorporated with a Class II MO restoration. The tooth model is triphasic, including the enamel, dentin, and pulp phases. To mimic the natural constraint on the movement of the tooth model, its corresponding mandible model has also been generated. The relative high maximum principal stress values were computed at the surface under loading and in the marginal region of the interface between the restoration and the tooth phases.